Determinants of Anxiety in Third-Trimester Pregnant Women in Bengkulu City - Oktavika, Endah Dwi; Maryani, Deni; Asmariyah; Suriyati; Saleha, Nurmukaromatis (Journal of Health Sciences and Medical Development, 2024)
Pregnancy-related anxiety is a prevalent mental condition characterized by apprehension and fear about uncertain events. Several factors contribute to anxiety in pregnant women, including Age, education, gravidity, husband's support, and spiritual self-care. This research aims to identify the influencing factors on anxiety levels in third-trimester pregnant women facing the birthing process in Bengkulu City, utilizing a cross-sectional approach. Forty-four respondents were selected through purposive sampling, and data were analyzed using the Spearman rank correlation test. The findings reveal significant relationships between Age (p-value 0.012 < 0.05), education (p-value 0.018 < 0.05), gravidity (p-value 0.026 < 0.05), husband's support (p-value 0.038 < 0.05), and spiritual self-care (p-value 0.000 < 0.05) and anxiety levels. In conclusion, Age, gravidity, education, husband's support, and spiritual self-care are associated with the anxiety levels of third-trimester pregnant women facing the birthing process in Bengkulu City.